Promotion Strategy for Cultural Tourism Packages in Tana Toa Kajang Village, Bulukumba Regency, South Sulawesi Province - Indrawan Wiratama; I Ketut Surata; I Wayan Mertha; Hilda Apriani (Dinasti Publisher, 2025)
This study aims to determine effective promotional strategies to enhance the appeal of cultural tourism and analyze the application of digital media in promoting cultural tourism packages in Tana Toa Kajang Village, Bulukumba Regency. This village is a traditional area with strong and unique cultural potential, but still faces various challenges in terms of tourism promotion. This study used a qualitative approach. Data collection techniques were carried out through in-depth interviews, field observations, and documentation. Research informants consisted of tourism managers, traditional leaders, local business actors, and tourists. Data were analyzed using the interactive model of Miles and Huberman (2010), which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the promotional strategies implemented are still conventional and not optimally structured. However, there are efforts to use social media such as Instagram and TikTok to introduce cultural attractions and tourist activities to a wider audience. However, limited human resources and digital infrastructure remain obstacles to the development of digital media-based promotions. With the right and culture-based promotional approach, Tana Toa Kajang Village has the potential to become a leading cultural tourism destination in South Sulawesi.